2015
DOI: 10.2172/1177382
|View full text |Cite
|
Sign up to set email alerts
|

Competing Quantum Hall Phases in the Second Landau Level in Low Density Limit

Abstract: Abstract:In this Rapid Communication we present the results from two high-quality, low-density GaAs quantum wells. In sample A of electron density n=5.010 10 cm -2 , anisotropic electronic transport behavior was observed at =7/2 in the second Landau level. We believe that the anisotropy is due to the large Landau level mixing effect in this sample. In sample B of density 4.110 10 cm -2 , strong 8/3, 5/2, and 7/3 fractional quantum Hall states were observed. Furthermore, our energy gap data suggest that, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Since samples from Refs. [28,53] had a wider quantum well than our samples, the nematic in them either does not develop or it forms at a yet unknown critical κ and w/l B parameters. The other two samples, however, had quantum wells of the same width as our samples [42,52].…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Since samples from Refs. [28,53] had a wider quantum well than our samples, the nematic in them either does not develop or it forms at a yet unknown critical κ and w/l B parameters. The other two samples, however, had quantum wells of the same width as our samples [42,52].…”
Section: Introductionmentioning
confidence: 56%
“…This was surprising, since in the second orbital Landau level at ν = 5/2 and 7/2 tilted field experiments suggested that the two ground states are close in energy [26,27]. Additionally, incipient nematicity was seen at ν = 7/2 [28]. However, a phase transition from the FQHS to the nematic in the absence of an in-plane symmetry breaking magnetic field was only recently observed [29].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, the development of the ordered phase with the application of an external magnetic field is not associated with a thermodynamic singularity. In the 2DEG spontaneous anisotropy develops in the absence of any externally applied symmetry breaking fields at ν = 9/2, 11/2, 13/2, 15/2, ... [5][6][7] and also at ν = 7/2 [30] at low enough temperatures. The ground state at these filling factors is the well-known quantum Hall nematic phase, also referred to in the literature as the stripe phase [1,2].…”
mentioning
confidence: 99%
“…The related studies at the 5/2 state have found much stronger evidence for spin-polarization than spin-unpolarization in open geometry samples (29)(30)(31)(32)(33)(34)(35)(36)(37). It should be noted that such an energy gap measurement (28) was studied at magnetic field lower than 1 T, and another measurement at magnetic field similar to this work only showed monotonic behavior between the energy gap and the density (38). Lastly, the electrostatic potential caused by the gates will certainly not be constant over the width of the confined region, and its shape may influence the relative stability of the two states.…”
Section: Discussionmentioning
confidence: 91%